A Test of General Strain Theory in South Korea: A Focus on Objective/Subjective Strains, Negative Emotions, and Composite Conditioning Factors. (June 2017) - Moon, Byongook; Morash, Merry
Few tests of General Strain Theory (GST) have examined the relative effects of objective and subjective strains on delinquency and the mediating effects of situational-based negative emotions linking strains to delinquency. With a sample of approximately 800 Korean adolescents, the present study tests a model that includes five key objective and the corresponding subjective strains identified as most predictive of delinquency, and situational-based anger and depression in response to each strain. Regardless of whether conceptualized as objective or subjective, three strains (teachers' punishment, gender discrimination, and criminal victimization) have positive effects on delinquent behaviors. No indicators of situational-based anger and depression (except anger in response to victimization in a negative direction) have direct effects on delinquency or have mediating effects linking strains to delinquency. The results provide limited support for GST's specification of the relatively greater effects of subjective than objective strains on delinquency and mediating effects of situational-based negative emotions. Theoretical implications are discussed.